Comparison of the calculations results of heat exchange between a single-family building and the ground obtained with the quasi-stationary and 3-d transient models. Part 2: intermittent and reduced heating mode = Porównanie wyników obliczeń wymiany ciepła jednorodzinnego budynku mieszkalnego z gruntem uzyskanych za pomocą metody quasi-stacjonarnej oraz modelu niestacjonarnego trójwymiarowego. Część II: ogrzewanie przerywane i przerwa w ogrzewaniu - Staszczuk, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper provides comparative results of calculations of heat exchange between ground and typical residential buildings using simplified (quasi-stationary) and more accurate (transient, three-dimensional) methods. Such characteristics as building?s geometry, basement hollow and construction of ground touching assemblies were considered including intermittent and reduced heating mode.
Keywords: heat transfer; quasi-stationary calculations; transient 3-D calculations; intermittent heating mode; reduced heating mode; wymiana ciepła; obliczenia quasi-stacjonarne; obliczenia trójwymiarowe; tryb ogrzewania